Negosiasi Medis dan Budaya: Konstruksi Sosial Tradisi Nyapih dan Eksistensi Jamu Juliang pada Masyarakat Jawa di Kebumen - Vidyambara Satyasih Wijaya; Fadly Husain (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze weaning practices (nyapih or mareni) as a socially constructed health practice within Javanese society in Karanganyar Village, Kebumen Regency. Specifically, the study examines the cultural meanings and social norms underlying weaning practices, identifies the role of traditional herbal medicine—particularly Jamu Juliang—as a form of local health knowledge, and explores the role of maternal knowledge and family support in shaping weaning decisions. The research employed a qualitative descriptive approach using observation, in-depth interviews, and documentation. The findings reveal that weaning is generally conducted when children reach approximately two years of age and is perceived as an important transitional phase in a child’s life course. Traditional herbal medicine plays an integral role in the weaning process, believed to alleviate children’s discomfort and support maternal health. Weaning practices are influenced by mothers’ knowledge of breastfeeding, beliefs in traditional medicine, and the role of family and community in decision-making processes. This study demonstrates that weaning is not merely a biological process but a socially constructed health practice shaped by cultural values, local knowledge, and social relations. These findings contribute to medical anthropology by highlighting culturally embedded child-care practices in Javanese communities.